1,25-Dihydroxyvitamin D3 Restrains CD4+ T Cell Priming Ability of CD11c+ Dendritic Cells by Upregulating Expression of CD31 - Saul, Louise; Mair, Iris; Ivens, Alasdair; Brown, Pamela; Samuel, Kay; Campbell, John D. M.; Soong, Daniel Y.; Kamenjarin, Nadine; Mellanby, Richard J. (Frontiers in Immunology, 2019)
Dendritic cells (DC) are specialized sentinel cells that bridge the innate and adaptive immune response and play a crucial role in shaping the adaptive immune response. Vitamin D, a known epidemiological risk factor for the development of several autoimmune diseases, influences the development of dendritic cells. Consequently, vitamin D metabolites are frequently used in protocols to develop therapeutic dendritic cell therapies for autoimmune diseases. However, the mechanisms by which vitamin D modulates DC function remain poorly understood. We investigated the effects of vitamin D on murine CD11c+ bone marrow derived DC (BMDC) function by analyzing global gene expression in CD11c+ BMDC generated in the presence (VitD-CD11c+BMDC) or absence (Veh-CD11c+BMDC) of the active vitamin D metabolite, 1,25-dihydroxyvitamin D3 (1,25(OH)2D3). Seven genes were significantly increased in expression in both immature and LPS-matured VitD-CD11c+BMDC, one of which was CD31, a member of the immunoglobulin superfamily. Gene knockdown of CD31 enhanced the ability of VitD-CD11c+BMDC to prime naïve CD4+ T cells in vitro; conversely, increased expression of CD31 on vehicle treated CD11c+BMDC restrained their T cell priming abilities. Time-lapse imaging of BMDC and CD4+ T cells during in vitro priming revealed that CD31 reduced the BMDC–T cell interaction time. Finally, we confirmed a similar effect of 1,25(OH)2D3 on human CD34+ cell-derived CD11c+DC, whereby DC generated in the presence of 1,25(OH)2D3 had increased CD31 expression. In summary, we show that both mouse and human DC generated in the presence of 1,25(OH)2D3 upregulate CD31 expression, resulting in a reduced ability to prime CD4+ T cells by impairing a stable cell-cell contact.